2016
DOI: 10.1007/s00704-016-1801-2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of four northern-hemisphere teleconnection patterns on atmospheric circulations over Eurasia and the Pacific

Abstract: The impacts of four teleconnection patterns on atmospheric circulation components over Eurasia and the Pacific region, from low to high latitudes in the Northern Hemisphere (NH), were investigated comprehensively in this study. The patterns, as identified by the Climate Prediction Center (USA), were the East Atlantic (EA), East Atlantic/ Western Russia (EAWR), Polar/Eurasia (POLEUR), and Scandinavian (SCAND) teleconnections. Results indicate that the EA pattern is closely related to the intensity of the subtro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…This study does not look into the physical processes that enable the AMO to influence the SLP variations over the Great Basin and the subtropical Pacific; however, prior studies have offered clues on the possible processes for the influence. For example, Zhang and Delworth (2007) suggested that the AMO can impact the North Pacific climate by altering the latitudinal location of the mid-latitude jetstream, while Yu et al (2015) and Gao et al (2016) noticed that the positive phase of the AMO can intensify the PSH. The mass redistribution associated with such a location shift and intensification may affect the strength of the SLP over the Great Basin and subtropical Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…This study does not look into the physical processes that enable the AMO to influence the SLP variations over the Great Basin and the subtropical Pacific; however, prior studies have offered clues on the possible processes for the influence. For example, Zhang and Delworth (2007) suggested that the AMO can impact the North Pacific climate by altering the latitudinal location of the mid-latitude jetstream, while Yu et al (2015) and Gao et al (2016) noticed that the positive phase of the AMO can intensify the PSH. The mass redistribution associated with such a location shift and intensification may affect the strength of the SLP over the Great Basin and subtropical Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…Other northern-hemisphere teleconnection patterns that are not zonally aligned but have arc-like shapes include the East Atlantic, East Atlantic/Western Russia, Polar/Eurasia, and Scandinavian patterns. Their influence on the atmospheric circulation over Eurasia and the Pacific was examined by Tao et al (2016). A wave train resembling the Scandinavian pattern was also identified by Wang and Feng (2011) who found that winter precipitation in south China is associated with a barotropic wave train originating over the Atlantic.…”
Section: Introductionmentioning
confidence: 94%
“…The im pacts of the EAWR pattern on the climate reach the mid-latitudes of East Asia as a planetary-scale stationary wave pattern (Krichak et al 2014), and the EAWR pattern is closely linked to summer precipitation over East Asia (Gao et al 2017, Tan & Shao 2017. Regarding the positive EWD pattern, an increase in its frequency leads to anomalous northerly flows prevailing in eastern China and significant anomalous easterly winds from the Bay of Bengal to the western Pacific, reducing the northward propagation of southerly water vapor transport from the tropics and leading to below-average precipitation in northern China (Figs.…”
Section: Ewd Patternmentioning
confidence: 99%